1999
DOI: 10.1006/qres.1998.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene Precipitation Balance in the Amazon Basin Recorded in Deep Sea Sediments

Abstract: Terrigenous sediments from Ceara Rise in the western tropical Atlantic Ocean record Pleistocene Amazon Basin climate variability. Iron oxides and oxyhydroxides in this region originate mainly from chemically leached Amazon lowland soils. Concentrations of goethite and hematite in the terrigenous fraction consistently peak during transitions from glacial to interglacial periods, suggesting an increased proportion of erosive products derived from the Amazon lowlands compared to the physically weathered highlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 52 publications
7
60
1
2
Order By: Relevance
“…The monsoon feeds off this moisture source and is, hence, strengthened at 506 ka. The South American DJF monsoon is enhanced in the MIS-13 experiments, endorsing the paleo-observations of wetter conditions from the Amazon basin (Harris and Mix 1999). The terrigenous sediments from the Ceara Rise off the Brazilian coast mainly originate from the Amazon lowlands, having been transported by the Amazon River.…”
Section: The Mis-13 Climate a Model Climatology And Comparison To Gesupporting
confidence: 75%
See 2 more Smart Citations
“…The monsoon feeds off this moisture source and is, hence, strengthened at 506 ka. The South American DJF monsoon is enhanced in the MIS-13 experiments, endorsing the paleo-observations of wetter conditions from the Amazon basin (Harris and Mix 1999). The terrigenous sediments from the Ceara Rise off the Brazilian coast mainly originate from the Amazon lowlands, having been transported by the Amazon River.…”
Section: The Mis-13 Climate a Model Climatology And Comparison To Gesupporting
confidence: 75%
“…There is a DJF increase in precipitation of 0.5-3.0 mm day 21 over the Amazon lowlands in the MIS-13 no-ice model, as seen in Fig. 2d, the model hence lends support to the data of Harris and Mix (1999). With regards to sea ice, there is an increase in the northward extent and amount in the Southern Ocean throughout the whole year.…”
Section: The Mis-13 Climate a Model Climatology And Comparison To Gesupporting
confidence: 61%
See 1 more Smart Citation
“…While this temperature-diversity relationship may be causal, it is also possible that diversity is instead driven by some other environmental driver that, like temperature, tracks glacial-interglacial cycles. Such factors might be mediated by latitudinal shifts in the Intertropical Convergence Zone (ITCZ) and changes in North Brazil Current (33,47), or changes in deep water characteristics reflecting the relative influence of North Atlantic Deep Water (NADW) versus Antarctic Bottom Water (AABW) (48,49). NADW and AABW differ in temperature, nutrients contents, and salinity, although at present there is not much evidence that nutrients and salinity have much influence on deep-sea diversity.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of small amounts of goethite and/or hematite measurably alters the first derivative spectrum of color reflectance in the visible light range . Derived from color reflectance spectra, the fraction of goethite in the total iron oxide [G / (G + H)] has therefore been used as a terrestrial precipitation indicator and has been demonstrated to be useful in Amazon Basin sediment studies (Harris and Mix 1999).…”
Section: Color Spectrum Estimations For Goethite and Hematitementioning
confidence: 99%